Implementation Of Uks Trias In Elemnetary School 22 Lubuk Minturun - Erita, Desnida; Putra, Randi Meidya; Rasyid, Willadi (Jurnal Guru Peneliti Professional, 2018)
The problem in this research is that the implementation of the UKS TRIAS is not yet optimal in SD Negeri 22 Lubuk Minturun, Koto Tangah District, Padang City. The purpose of this study was to describe the implementation of health education, health services, and a healthy school environment in SD Negeri 22 Lubuk Minturun, Koto Tangah District, Padang City. This study used a descriptive type of research, namely to reveal and explain the implementation of UKS in SD Negeri 22 Lubuk Minturun, Koto Tangah District, Padang City. The population in this study were all students in grade IV and V at SD Negeri 22 Lubuk Minturun, Koto Tangah District, Padang City, totaling 62 people. The sample technique used was a total sampling of 62 people. The data collection tool was a questionnaire using the Guttman scale model with the answer categories "yes" and "no". Furthermore, the data were processed and analyzed using descriptive statistical techniques. Data analysis at SD Negeri 22 Lubuk Minturun, Koto Tangah District, Padang City, among others: (1) 92.9% stated that health education has been implemented and 7.07% of respondents health education has not been implemented. (2) 85.5% of respondents stated that health services had been implemented and 14.5% of respondents stated that health services had not been implemented. (3) 97.2% of respondents stated that the coaching of a healthy school environment had been carried out while 2.82